Ecología trófica en larvas de Rhinella arenarum (Anura: Bufonidae) en agroecosistemas y sus posibles implicancias para la conservación - Bionda, Clarisa de Lourdes (2012)
The progress of the agriculture border has led an important loss of natural habitats, with significant consequences for biodiversity. In this sense, the studies in anuran amphibian tadpoles inhabiting these environments are relevant, because the larval stage is a phase of population regulation. The aim of this study was to analyze the body condition and diet in Rhinella arenarum, tadpoles, an anuran species widely distributed in South America and that inhabit agroecosystems. Three sites were sampled, two agroecosystems with different alteration degrees (C1 and C2) and an uncultured (SM) third place. The captured tadpoles were anesthetized, fixed and preserved in formaldehyde (10%). Subsequently, body measurements were made and the complete intestine was removed and analyzed for food items under a binocular microscope. The diet in R. arenarum tadpoles has a dominance of algae Bacillariophyceae, followed by Cyanophyceae. In particular, the class Bacillariophyceae, due to the presence of the genus Navicula, Nitzschia, Gomphonema and Hantzschia, was important in the diet of the anurans in those agroecosystems. Class Cyanophyceae, mainly represented by genus Oscillatoria and Euglenophyceae represented by Euglena and Strombomonas, were predominant in the diet of the anurans in SM. Some differences in the total items consumed by tadpole were observed between the studied sites. Tadpoles that inhabit the modified sites (C1 and C2) recorded a significantly smaller amount of food. Moreover, the tadpoles that inhabit these sites showed a lower body condition. The presence of certain algae associated with eutrophic environments, could indicate some pollution in agroecosystems (C1 and C2). Food resources would be lesser in places with strong agricultural activity, possibly with a greater degree of eutrophication. A smaller food amount could have consequences at population level for the short and long time terms, because of its impact on individual growth. Larval diet is suggested as a potential bioindicator of environmental health for these areas.